2016
DOI: 10.18632/oncotarget.13272
|View full text |Cite
|
Sign up to set email alerts
|

Bisdemethoxycurcumin exerts pro-apoptotic effects in human pancreatic adenocarcinoma cells through mitochondrial dysfunction and a GRP78-dependent pathway

Abstract: Pancreatic cancer is a highly aggressive malignancy, which is intrinsically resistant to current chemotherapies. Herein, we investigate whether bisdemethoxycurcumin (BDMC), a derivative of curcumin, potentiates gemcitabine in human pancreatic cancer cells. The result suggests that BDMC sensitizes gemcitabine by inducing mitochondrial dysfunctions and apoptosis in PANC-1 and MiaPaCa-2 pancreatic cancer cells. Utilizing two-dimensional gel electrophoresis and mass spectrometry, we identify 13 essential proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…GRP78 (BiP) is a 78-kDa protein chaperone [26,27] that has been proven to prevent the cell death caused by disturbance of endoplasmic reticulum (ER) homeostasis [28] and to mediate essential components of ER stress-induced apoptosis [31][32][33]. Fluorescent labeling and immunofluorescence staining indicated that TTR efficiently crossed cell membrane and nuclear membrane; the localization of TTR and GRP78 partially overlapped in and around the nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 (BiP) is a 78-kDa protein chaperone [26,27] that has been proven to prevent the cell death caused by disturbance of endoplasmic reticulum (ER) homeostasis [28] and to mediate essential components of ER stress-induced apoptosis [31][32][33]. Fluorescent labeling and immunofluorescence staining indicated that TTR efficiently crossed cell membrane and nuclear membrane; the localization of TTR and GRP78 partially overlapped in and around the nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…It was also associated with elevated poly ADP‐ribose polymerase (PARP) and cleaved caspase‐3. Moreover, BDMC was found to greatly enhance the antitumor effects of GEM in both cell lines …”
Section: Curcuminoidsmentioning
confidence: 97%
“…Another study reported that the BDMC-gemcitabine (GEM) combination induced the greatest mitochondrial dysfunction and apoptosis in PANC-1 and MIA PaCa-2 cells. 23 Apoptosis was observed in greater than 60% of the cell lines treated with BDMC-GEM. It was also associated with elevated poly ADPribose polymerase (PARP) and cleaved caspase-3.…”
Section: Curcuminoidsmentioning
confidence: 98%
See 1 more Smart Citation
“…The influence of curcumin on multiple cellular pathways like NFkB-, PI3-kinase-or p53-activity leading to inhibition of proliferation and induction of apoptosis was shown in preclinical models of different tumor entities, including pancreatic cancer [13][14][15] . In addition, impact on formation of reactive oxygen species, regulating RNAs, mitochondrial function, cell membrane and epigenetic changes were described using Curcumin in tumor cell treatment [16][17][18][19][20] . Some in vitro studies demonstrated radiosensitization by Curcumin, e.g.…”
mentioning
confidence: 99%